Long‐term Impacts of Permafrost Thaw on Carbon Storage in Peatlands: Deep Losses Offset by Surficial Accumulation. Issue 3 (20th March 2020) - Heffernan, Liam; Estop‐Aragonés, Cristian; Knorr, Klaus‐Holger; Talbot, Julie; Olefeldt, David
Abstract: Peatlands in northern permafrost regions store a significant proportion of global soil carbon. Recent warming is accelerating peatland permafrost thaw and thermokarst collapse, exposing previously frozen peat to microbial decomposition and potential mineralization into greenhouse gases. Here, we show from a site in the sporadic‐discontinuous permafrost zone of western Canada that thermokarst collapse leads to neither large losses nor gains following thaw, as deep carbon losses are offset by surficial accumulation. We collected peat cores along two thaw chronosequences, from peat plateau, through young ( 30 years since thaw), intermediate ( 70 years), and mature ( 200 years) thermokarst bog locations. Macrofossil and 14 C analysis showed synchronicity of peatland development until recent thaw, with wetland initiation 8, 500 cal yr BP followed by succession through peatland stages prior to permafrost aggradation 1, 800 cal yr BP. Analysis and modeling of soil carbon stocks indicated 8.7 ± 12.4 kg C m −2 of carbon accumulated prior to thaw was lost in 200 years post‐thaw. Despite these losses, there was no observed increase in peat humification as assessed by Fourier transform infrared and C:N ratios. Rapid peat accumulation post‐thaw (9.8 ± 1.6 kg C m −2 over 200 years) offset deeper losses. Our approach constrains the net carbon balance to be between uptake of 27.3 g C m −2 yr −1 and loss of 106.6 g C m −2 yr −1 over 200 years post‐thaw. While our approach cannot determine whether thermokarst bogs in the sporadic‐discontinuous permafrost zone act as long‐term carbon sinks or sources post‐thaw, our study better constrains post‐thaw C losses and gains. Plain Language Summary: Northern peatlands store a third of the world's soil carbon, a store which has slowly accumulated over the last 10, 000 years. A large amount of this soil carbon has become frozen in permafrost peatlands, but warming is causing these stores to thaw. Permafrost thaw in peatlands not only leads to potential decomposition of previously frozen peat but also leads to increased growth of mosses at the surface. Increased decomposition of previously frozen peat can release formerly trapped carbon into the atmosphere as greenhouse gases, thus accelerating ongoing climate warming, while increased moss growth would increase carbon storage. In this study, we investigated the long‐term impact of thawing on peatland carbon storage. To do this, we measured the amount of previously frozen permafrost carbon that was lost following thaw and compared it to the amount that accumulated at the surface. We found no long‐term net impact of permafrost thaw on carbon stores, as losses of previously frozen carbon were offset by carbon that accumulated at the surface following thaw. Our results rule out both large rapid losses and large gains of carbon following thaw in peatlands, which greatly help to constrain projections of carbon cycling at high latitudes in a warming world. Key Points: We used a chronosequence approach to assess the long‐term impact of permafrost thaw on peatland carbon stores Losses of deep carbon offset by accumulation at the surface following thaw We rule out large losses and gains of carbon following permafrost thaw at a site with a history of epigenetic permafrost aggradation